Conformation effects of CpG methylation on single-stranded DNA oligonucleotides: analysis of the opioid peptide dynorphin-coding sequences. - Malik Mumtaz Taqi (Public Library of Science (PLoS), 2012)
Single-stranded DNA (ssDNA) is characterized by high conformational flexibility that allows these molecules to adopt a variety of conformations. Here we used native polyacrylamide gel electrophoresis (PAGE), circular dichroism (CD) spectroscopy and nuclear magnetic resonance (NMR) spectroscopy to show that cytosine methylation at CpG sites affects the conformational flexibility of short ssDNA molecules. The CpG containing 37-nucleotide PDYN (prodynorphin) fragments were used as model molecules. The presence of secondary DNA structures was evident from differences in oligonucleotide mobilities on PAGE, from CD spectra, and from formation of A-T, G-C, and non-canonical G-T base pairs observed by NMR spectroscopy. The oligonucleotides displayed secondary structures at 4°C, and some also at 37°C. Methylation at CpG sites prompted sequence-dependent formation of novel conformations, or shifted the equilibrium between different existing ssDNA conformations. The effects of methylation on gel mobility and base pairing were comparable in strength to the effects induced by point mutations in the DNA sequences. The conformational effects of methylation may be relevant for epigenetic regulatory events in a chromatin context, including DNA-protein or DNA-DNA recognition in the course of gene transcription, and DNA replication and recombination when double-stranded DNA is unwinded to ssDNA.